CORRELATION AND CAUSALITY BETWEEN CONSUMER SENTIMENT AND STOCK MARKETS: EVIDENCE FROM SP 500 - Laaksoharju, Maarit (My University, 2012)
The purpose of thesis is to investigate the relationship and causality between two im-portant consumer sentiment indices and the stock markets in United States. Used measures are monthly observations of Michigan Consumer sentiment MCSI and Con-ference board Consumer Confidence CCI. SP500 will represent the stock market and it will be divided in to 11 sector subsets to provide view in to the relationship among dif-ferent industries. Statistical methods used in this thesis are correlation and Granger cau-sality.
Keywords: Consumer confidence; Granger causality; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|